SULUK SEBAGAI SISTEM RELIGI PADA MASYARAKAT DESA RAMBAH HILIR TENGAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Aminatul Islam; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted in the village of Rambah Hilir Tengah in the Rambah Hilir District, Rokan Hulu Regency. The purpose of this study is to determine the suluk tradition is a tradition that reflects a way of worship. The focus topic of this research is Suluk as a Religious System. The sample in this study amounted to 5 people. Researchers used qualitative methods and used purposive sampling technique. The data instruments were observation, interview and documentation. Research finds that suluk as a religious system is a social act as follows. Value-oriented action. Instrumental action. Traditional action and affective action. And suluk is also a tradition in the group of bersareqat and at the same time worship such as making dhikr, praying, praying, istighfar, and other practices. And also in suluk teaches to strengthen friendship between others, love to help, lifestyle, amar ma'ruf nahi munkar, and other practices and can be a good example for the surrounding community. Tradition Is a tradition that has been passed down from generation to generation, and in the village of Rambah downstream, Rambah downstream, Rokan Hulu district always carries out suluk activities in the surau surau.Key words: Suluk as a religious system, Social Action.